Reconfiguring Rivalry: Ideological Sorting, Digital Media, and the New Landscape of Affective Polarization in the Post-2024 Presidential Election in Indonesia - Ervin Munandar; Yuniarti Maretha Pasaribu; Firzan Dahlan; Aaliyah El-Hussaini (HM Publisher, 2025)
The 2024 Indonesian presidential election marked a tectonic shift in its political landscape, dissolving the decade-long 'Cebong versus Kampret' rivalry. This study investigates whether this realignment led to depolarization or a reconfiguration of partisan animosity. It examines the structure and predictors of affective polarization in the immediate post-election environment. A cross-sectional survey was conducted from May to July 2024, involving 1,500 respondents across 15 provinces, selected via a multi-stage random sampling method with probability proportional to size. Affective polarization was measured using a feeling thermometer scale. Key predictors—including ideological self-placement, social media consumption for political news, and intergroup contact—were analyzed using hierarchical multiple regression. To test for non-linear ideological effects, both linear and quadratic terms for ideology were included in the model. The analysis reveals that affective polarization remains a potent force. The regression model showed a strong fit (R2= 0.47). While a linear measure of ideology was not a significant predictor, its quadratic term was a powerful and positive predictor (b = 0.42, p<0.001), indicating a U-shaped relationship where individuals at both ideological poles exhibit significantly higher polarization than those in the center. High consumption of partisan social media was also strongly associated with increased polarization (b = 0.35, p<0.001), while quality intergroup contact was linked to lower levels (b = -0.21, p<0.001). In conclusion, the post-2024 political era in Indonesia is characterized by a reconfiguration, not a dissipation, of affective polarization. The cleavage is no longer primarily personality-driven but is increasingly structured by ideological sorting, amplified by digital media ecosystems. These findings highlight the need for initiatives promoting cross-cutting dialogue and digital literacy to safeguard democratic health.